Self-awareness and its relationship to aggressive behavior among Palestinian adolescents - Sweilim, Saeed Yousef (Journal of Humanities & Social Sciences, 2025)
The research aimed to examine the nature and direction of the relationship between self-awareness and aggressive behavior. The research sample consisted of (100) male and female adolescents, who were randomly, selected, from the northern governorates of the West Bank - Palestine. The research used the self-awareness scale prepared by Al-Khalidi (2014) and the aggressive behavior scale prepared by Amal Baza (2003). The descriptive analytical approach has been used and the reliability coefficient was calculated using the coefficient (Cronbach’s alpha), where the stability value of the scale of self-awareness was (0.78) and the scale of aggressive behavior was (0.96), and this is considered sufficient for the purposes of the research. The results showed an inverse correlation between self-awareness and aggressive behavior, and the absence of statistically significant differences in self-awareness and aggressive behavior among the sample of adolescents due to the variables of gender, place of residence, age, and educational level,The recommendations underscore the imperative to organize workshops, seminars, and targeted training programs for teaching staff aimed at fostering self-awareness and managing aggressive behavior within classroom settings. Furthermore, they call for the pursuit of additional empirical research focusing on adolescents and the factors contributing to the manifestation of aggressive behavior in the Palestinian context, as well as examining these factors in relation to other relevant variables.